قواعد المآلات وتطبيقاتها في المعاملات المالية المعاصرة: The Legal maxims of Maʾālāt and its Contemporary Application on Financial Transactions - Mahamed Fathy Eletrebi; Hassan Suleiman; Abdul Bari bin Awang (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
لماكان ديننا الحنيف حكمة وفقهاً؛ فإن من الحكمة أن ينظر المسلمون إلى مستقبلهم وما تؤول إليه أفعالهم وتصرفاتهم -بعد الاستفادة من تجارب الماضى وخبرات الحاضر– باستشرافه ومنازعته والاستعداد له بما يحتاجه من علوم وفنون تضمن لهم اجتماعا بشرياً راقياً، فالرجل من يكون منازعاً للقدر، لا من يكون مستسلماً مع القدر كما قال العارف بالله عبد القادر الكيلانى! من هنا كان اهتمامنا بالمآلات وقواعدها الأصولية وتطبيقاتها المالية المعاصرة. أما هدف الدراسة،فهو توظيف معارفنا الإسلامية الأصولية والمقاصدية والفقهية والفكرية فى تكييف فقهي لأبرز المعاملات المعاصرة. لذا فإن إشكالية البحث هى: ما دور قواعد المآلات في النظرة الفقهية للمعاملات المعاصرة. منهج البحث فهو المنهج الاستقرائي التحليلي الاستنباطي؛ وذلك باستقراء النصوص الشرعية المؤسسة لاعتبار المآلات ثم تحليل تلك النصوص لاستنباط الأحكام المناسبة للمعاملات المالية المعاصرة. وأبرز النتائج: أولاَ: أن الإسلام هيأ الإنسان للنظر في المآلات وحرره من معوقات الخرافة والتشاؤم والتطاير والتنجيم وعليه ألا يستسلم ويخضع، بل يواجه ويجاهد بالحق وللحق. ثانياً: أن قواعد المآلات تهدف إلى النظر في الأحكام الشرعية المتعلقة بالغد الصادق وما يمكن وقوعه من أفعال المكلفين المبنية على عبر الماضى وتفهم الواقع واستشراف القادم حسب الطاقة الممكنة. ثالثا: أن القرآن الكريم اهتم بالسنن الكونية والاجتماعية باعتبارها إرهاصات للمآلات ومعنيات على تصورها، كما اهتم بالزمن بكل أجزائه الماضى والحاضر والمستقبل كى يكون المسلم على بنية من أمره فى حركته، وسكنته، وأسبابه، ونتائجه. الكلمات المفتاحية: القواعد- المآلات- المقاصد-الاستحسان-المصلحة- الذرائع -الحيل- المالية –المعاصرة. Abstract Our religion with its wisdom and jurisprudence; it is wise for Muslims to look at their future and what their actions and behavior will lead to - after benefiting from the experiences of the past and the experiences of the present - by anticipating it and challenging it and preparing for it with what it needs of sciences and arts that guarantee them a sublime human meeting, as Abdulqadir Al-Kilani said. Hence our interest in the outcomes and their fundamentalist rules and contemporary financial applications. As for the study’s goal, it is to employ our Islamic fundamental, intentional, jurisprudential and intellectual knowledge in a jurisprudential adaptation of the most prominent contemporary transactions. Therefore, the research problem is: What is the role of the rules of fate in the jurisprudential view of contemporary transactions. The research method is inductive, analytical, and deductive method. By extrapolating the legal texts established to consider the outcomes and then analyzing those texts to derive appropriate provisions for contemporary financial transactions. The most prominent results: First: that Islam prepared man to consider the fates and freed him from the obstacles of superstition, pessimism, volatility, and astrology. Second: The rules of fate aim to consider the legal rulings related to the true tomorrow and the possible actions of the taxpayers based on the past, understanding the reality and anticipating the future according to the possible capacity. Third: The Holy Qur’an was concerned with the cosmic and social norms as harbingers of the fates and the meanings of their perception, as it was concerned with time in all its parts, past, present and future, so that the Muslim would be on the basis of his order in his movement, his residence, its causes, and its consequences. Keywords: Rules, Outcomes, Intentions, Approval, Interest, Pretexts, Tricks, Financial, Contemporary.